Relawan Pajak Mengabdi : “Pendampingan Pelaporan SPT Orang Pribadi di KPP Pratama Bangkalan” - Sophie Damayanti, Wilda; Carolina, Anita (LPPM ITB AAS Indonesia Surakarta, 2025)
Tax is the main source of income for the state, so one of the responsibilities of taxpayers who have a NPWP is to report their tax obligations every year. Reporting of the OP Annual Tax Return is done online on the DJP Online website via E-Filling. There is a deadline for reporting the OP Annual Tax Return, which is March 31 each year. The types of forms used 1770S and 1770SS depend on the type of income of each Individual Taxpayer. This online tax report filling procedure is faster and better, but not all Taxpayers are able to do it themselves, especially for those who are elderly and have difficulties. As a result, a number of Taxpayers decide to visit the Tax Service Office (KPP) in person to report. As a result, the Tax Service Office launched the Tax Volunteer initiative to provide support to Taxpayers in submitting their Individual Annual Tax Returns at the KPP throughout the tax period.